BUDAYA ORGANISASI SEBAGAI MEDIASI KEPEMIMPINAN TERHADAP KINERJA KARYAWAN - Endang Setyo Wati; Endi Sarwoko; Yuni Mariani Manik (CAPITAL: Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to identify and analyze about (1) The effect of leadership on employee performance. (2) The influence of leadership on employee performance through organizational culture. Samples were taken using a sample proposition method. The selected respondents were employees of PT Ramayana Lestari Sentosa who had worked for more than 3 years. In this case the researchers took a sample of 170 respondents. The hypothesis of this study was tested using path analysis techniques. The results of this study indicate that leadership has a direct effect on employee performance. Organizational culture has a role in mediating the influence of leadership on employee performance significantly. Thus the role of organizational culture has an important role in improving employee performance.